Reactive Sorption on Functional Furan Resins - Ruben J.S. Rodriguez; Carlos Hernández; Victor Teixeira da Silva (Adsorption Science & Technology)
The immobilization of different substrates by specific interactions with insoluble functional supports has developed into quite an active research topic. In the present work, the interaction of two furanic resins obtained by acid catalysis from furfuraldehyde and furfuraldehyde–dimethylketone was studied at 0 °C and 30 °C. Both resins adsorbed ca. 10 −3 mol of ammonia at these temperatures and the adsorption process was characterized by a long period before equilibrium was attained, with the corresponding data being fitted by the Freundlich adsorption model. The structures of the resins were characterized using Fourier-transform infrared spectroscopy (FT-IR) and nuclear magnetic resonance (NMR) spectroscopy. Through the use of temperature-programmed desorption coupled with mass spectrometry (TPD–MS), it was possible to infer that ammonia adsorption modified the original chemical structure of the resins to yield imine structures as a result of the reaction of ammonia with the existing more reactive carbonyl groups.